Social Anomia against the Backdrop of Misinformation/ Disinformation: A Cognitive Approach to the Multivalent Data in Cyberspace - Parisa Amiri Fard (Cyberspace Studies, 2020)
The present study is an attempt to problematize the multivalent data in the cyberspace through the lenses of Wittgenstein’s analytic philosophy of language. Adopting this linguistic philosophy approach is aimed at exploring the dichotomous question of whether cyberspace is a possibility for social power or it is a contributory cause of communicative discontinuity and henceforth a possibility for social anomia. The central argument here is that within cyberspace there exist three languages at work each one with a degree of semiotic power: pictorial, verbal and mathematical. Since none of them is based on a one-to-one correspondence between the signifiers and the signifieds, the cyberspace users in practice are led to misinformation and disinformation instead of information. This situation creates an epistemic chasm in their real life. This is because their finite mind is not able to grasp the infinite reality of the cyberspace multivalent data. Accordingly, cyberspace with its abundance of misinformation and disinformation leads us to a mental disorder. This constitutes the real power of social media in creating a socio-political turmoil and anomia.